Proceedings of The Fourth International Technical Symposium on Deepwater Oil and Gas Engineering - Sun, Baojiang; Sun, Jinsheng; Wang, Zhiyuan; Chen, Litao; Chen, Meiping; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book is a compilation of selected papers from the Fourth International Technical Symposium on Deepwater Oil and Gas Engineering & The Third International Youth Forum on Gas Hydrate, held in Qingdao, China in December 2021. The work focuses on the advancement of techniques for the deepwater oil and gas exploitation and natural gas hydrate exploitation. The book introduces new ideas for exploring deepwater oil and gas hydrate in a safe and efficient way. Advances of the natural gas hydrate pilot production in South China Sea, in oil and gas flow assurance and emerging technologies based on clathrate hydrate will be presented. It is a valuable resource for both practitioners and academics working in the field of deepwater oil and gas engineering.
1. Deepwater Drilling and Completion -- 2. Natural Gas Hydrate Exploration and Reservoir Description -- 3. Natural Gas Hydrate Production Experiments and Numerical Simulation -- 4. Flow Assurance and Sand Production Control -- 5. Fundamentals and Emerging Technologies of Clathrate Hydrate.
Keywords: Offshore structures; Cogeneration of electric power and heat; Fossil fuels; Mining engineering; Oceanography; Chemical engineering; Power resources; Offshore Engineering; Fossil Fuel; Mining and Exploration; Ocean Sciences; Chemical Engineering; Natural Resource and Energy Economics; Petroleum engineering -- Congresses